PRECAMBRAIN FAULT SYSTEMS AS CONTROL ON REGIONAL DIFFERENCES IN RELATIVE SEA LEVEL ALONG THE EARLY ORDOVICIAN PLATFORM OF EASTERN NORTH AMERICA - Hersi O.S.; Dix G.R. (My University, 2006)
This study proposes that there was regional variation in Early Ordovician subsidence histories along eastern Laurentia controlled by broad differences in the susceptibility of inherited Precambrian crustal structure to reactivation with changing ocean-basin tectonism. Two continental-scale Phanerozoic fault systems (Southern Oklahoma Fault System, Ottawa-Bonnechère Graben) extend into the craton interior from the apices of the Ouachita and Quebec embayments or reentrants, respectively. Their traces identify reactivated Proterozoic fault zones. Previous studies show that rates of subsidence for Early Ordovician sedimentation along the axis of the Southern Oklahoma Fault System are elevated compared to regional rates beyond this structural corridor. A similar history applies to Early Ordovician sedimentation within the Ottawa Embayment (eastern Ontario), along the present axis of the Ottawa-Bonnechère Graben. The Theresa Formation (lower Beekmantown Group) contains a third-order peritidal (siliciclastic-dominated) sequence. Evidence for local tectonism prior to and during its development within the embayment includes: (1) Late Cambrian (pre-Theresa) preferential uplift, differential erosion, and subsidence along the eastern structural boundary of the embayment; (2) differential intrabasinal subsidence during Theresa deposition; (3) an apparent offset in timing of peak flooding within the embayment to that along the St. Lawrence Promontory, ~ 1500 km distant; and (4) absence of a subaerial unconformity in the embayment that otherwise separates eustatic cycles on the promontory, and defines a likely sea-level fall below the shelf margin. In comparison, subsidence within the embayment appears to have matched (at least) the rate of the eustatic fall. Regional differences in Early Ordovician subsidence histories along this margin may illustrate that the Precambrian fault zones were structurally more sensitive than promontories to the developing reconfiguration of oceanic lithospheric elements that would lead to the Taconic orogeny. Copyright © 2006, SEPM (Society for Sedimentary Geology).
Keywords: Proterozoic; Ordovician; Cambrian; Precambrian::Proterozoic; Докембрий::Протерозой; Paleozoic::Ordovician; Палеозой::Ордовикская; Paleozoic::Cambrian; Палеозой::Кембрийская